2018
DOI: 10.1111/hae.13472
|View full text |Cite
|
Sign up to set email alerts
|

Pain and structural alterations in knee joints in patients with haemophilia

Abstract: Particular degenerative changes in terms of osteophytes and thickness of synovial tissue are associated with an enhanced pain sensitivity in PwH. Altered PPT which were not associated with structural findings may be an indicator for a complex peripheral and/or central sensitization of the affected joints in PwH. The role of this mechanism should be clarified in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 35 publications
6
26
1
Order By: Relevance
“…Haemophilic patients suffer from emoarthropathies that lead them to have an increased sensitivity to pain. The somatosensory profile of these patients is impaired [21,22]. A later study by Roussel in 2018 still focused on pain, this study did not focus on joint bleeding as a cause of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Haemophilic patients suffer from emoarthropathies that lead them to have an increased sensitivity to pain. The somatosensory profile of these patients is impaired [21,22]. A later study by Roussel in 2018 still focused on pain, this study did not focus on joint bleeding as a cause of pain.…”
Section: Discussionmentioning
confidence: 99%
“…These instances of bleeding may lead to haemophilic arthropathy based on changes in joint function and structure caused by inflammatory processes of synovia as well as destruction of the cartilage tissue . The course of this process is associated with pain in PwH . While an acute bleeding episode results in acute pain, the individual's pain status can shift towards being recognized as a chronic pain condition, induced by haemophilic arthropathy .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The course of this process is associated with pain in PwH. 4 While an acute bleeding episode results in acute pain, the individual's pain status can shift towards being recognized as a chronic pain condition, induced by haemophilic arthropathy. 5 Recent studies pointed out that more than 85% of patients suffered from pain over a period of the last six months, and up to 89% reported that pain during the last 4 weeks interfered with activities in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity to pain in the knee joint in patients with haemophilia is accompanied by the presence of osteophytes and is linked to synovial hypertrophy. However, in the absence of structural changes there is an increased sensitivity to pain in the knee joints as a diffuse sign of peripheral or central sensitization 36 . Our study reports high values in the mean difference in perceived pain between the various evaluations in those patients who received manual therapy.…”
Section: Discussionmentioning
confidence: 47%
“…However, in the absence of structural changes there is an increased sensitivity to pain in the knee joints as a diffuse sign of peripheral or central sensitization. 36 Our study reports high values in the mean difference in perceived pain between the various evaluations in those patients who received manual therapy. This significant change points towards the suitability of this technique for the treatment of pain in patients with haemophilic knee arthropathy.…”
Section: Discussionmentioning
confidence: 55%